Relationship Between Finnish Diabetic Risk Score (FINDRISC) with Health-Related Quality of Life in Yogyakarta - Ninda Sari Wahyuningtyas; Dyah Aryani Perwitasari; Satibi Satibi (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2021)
The number of people with type 2 diabetes mellitus (T2DM) in Indonesia increases every year. Control of the development of T2DM can be done by screening using Finnish Diabetic Risk Score (FINDRISC)-Indonesian. FINDRISC is a valid tool for estimating the risk of T2DM within the next 10 years. This condition can have a major impact on the estimated life span and quality of life in the future. The purpose of this research is to determine the relationship between FINDRISC-Indonesian and respondent characteristics with HRQoL from EuroQol-5 Dimension-5 Level (EQ-5D-5L) in Yogyakarta. The cross-sectional study was conducted on 125 respondents who met the inclusion criteria. The risk of developing T2DM was assessed using a validated and widely used FINDRISC (range 0-26 points), and quality of life was measured by the EQ-5D-5L instrument. Overall data were analyzed using the Pearson correlation test and Independent t-test. The results showed the domain of pain was the domain that reported most respondents' most problems (28.8%). The respondent's utility value was 0.958 ± 0.69, and the VAS value was 79.4 ± 0.7. There was a significant difference in utility value based on age characteristics (p = 0.013). There was a relationship between age and utility value (p = 0.006) and FINDRISC score with utility value (p = 0.003). This study concludes that a high FINDRISC score affects the quality of life, and older age has a lower quality of life.